Prostatic stromal microenvironment and experimental diabetes - Ribeiro, D. L.; Caldeira, E. J.; Cândido, E. M.; Manzato, A. J. [UNESP]; Taboga, Sebastião Roberto [UNESP]; Alves Cagnon, V. H. (My University, 2006)
The diabetes causes alterations in various organ systems, including the male accessory sex glands. The prostate is very important in the reproductive process and it is a frequent target of malignant changes. The aim of this work was to demonstrate the histochemical and ultrastructural alterations in the prostate of diabetic animals. Two groups of animals were utilized: control and non-obese diabetic mice (NOD). Twelve days after the characterization of diabetic status the ventral prostate was collected, fixed in Karnovsky and paraformaldehyde, processed for histochemistry and TEM associated to stereology. The results showed reduction of the epithelial area and increasing of the stromal area with muscular and collagen hypertrophy in the prostatic gland. It was characterized the development of prostatic intraepithelial neoplasia, inflammatory processes and dilation of the organelles involved in the secretory process. It was concluded that diabetes besides damaging the reproductive process, affects the glandular homeostasis favoring the development of prostatic pathologies. ©2005, European Journal of Histochemistry.
Keywords: Diabetes; Histochemistry and ultrastructure; NOD mice; Prostate; Stroma; paraformaldehyde; animal cell; animal experiment; animal model; animal tissue; cell organelle; controlled study; experimental diabetes mellitus; histochemistry; homeostasis; male; mouse; nonhuman; prostate; prostate hypertrophy; prostate tumor; stereology; ultrastructure analysis and electron microscopy; Animalia; Mus